Linguistic manifestation of gender reinforcement through the use of the Japanese term kawaii - Asano-Cavanagh, Yuko (Equinox Publishing Ltd., 2014)
This paper examines the Japanese work kawaii 'cute'. Young Japanese women frequently say kawaii to express positive feelings towards objects or people. Scholars suggest that Japanese women are making kawaii a part of female gender identity. From a linguistic perspective kawaii is not lexicalised in other langauges. Although the kawaii phenomenon has been thoroughly examined, there has been no rigorous semantic analysis. The framework of the Natural Semantic Metalanguage approach was applied to explicate the exact meaning of kawaii for non-Japanese speakers. The analysis indicates that the core meaning of kawaii is linked to a notion of a 'child'. The associated emotion is explained as 'when I see this, I can't not feel something good'. The kawaii syndrome reveals a Japanese cultural characteristic which puts emphasis on being 'gender appropriate' in schools and society. The analysis has implications for understanding gender construction and expression in non-western cultures.